Dr. Omar Federico López Lugo — Deep Plane Facelift — Tijuana - López Lugo, Omar Federico (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Omar Federico López Lugo, practicing in Tijuana, Mexico. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003185; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; mexico; tijuana